Market capitalization growth and leverage level on the performance of automotive and component sub-sector shares - Suskim Riantani; Gusni Gusni; Siti Komariah (Institute of Computer Science (IOCS), 2023)
The performance of stocks, as measured by stock return, is a crucial factor and often a primary consideration for investors when making investment decisions. The potential for profit in investing is attainable when investments are made for the long term and in the right instruments. The objective of this research is to analyze the influence of market capitalization growth, measured by the value of stock price and tradable shares, and leverage level, measured using the debt to equity ratio, on stock performance measured by stock returns. The research methodology employs descriptive verification analysis with a quantitative approach. The study focuses on the manufacturing industry, specifically the automotive and component sub-sector, listed on the Indonesian Stock Exchange (IDX). Observations were carried out over the period 2015-2020, involving 12 stock issuers. The sampling method utilized was purposive sampling. Data analysis was conducted using panel data regression, with the application of an F-test to examine the research model and a t-test to evaluate the research hypotheses at a significance level of 5% alpha. The results of the model test demonstrate a good fit, allowing for the subsequent testing of research hypotheses. The research findings reveal that market capitalization growth (market cap) has a positive and significant correlation with stock performance, as measured by stock returns. On the other hand, the leverage level measured using the debtto equity ratio has not impacted stock performance.